SUSTAINABILITY OF ECONOMIC EDUCATION THROUGH DEVELOPMENT OF FAMILY BUSINESS MECHANISMS IN STUDENTS IMPROVE PLACE AND SIGNIFICANCE IN SOCIETY - Dilfuza BOBOKULOVA (Scholar Express Journal, 2023)
This article in students family entrepreneurship mechanisms development through economic education stability of improvement in society place and Regarding the fact that knowledge, innovation and methods of their practical application are more applicable as a source of income depending on the development of society, especially manifested in strong economic opportunities written
Keywords: Entrepreneurship; Vocational; Economic